1978
DOI: 10.1007/bf01641903
|View full text |Cite
|
Sign up to set email alerts
|

Protection of mice against tick-borne encephalitis by different classes of immunoglobulins

Abstract: The protective capacities of IgM and IgG immunoglobulins from fractionated human or mouse sera were investigated in tests with tick-borne encephalitis virus. Mice were resistant to challenge with tick-borne encephalitis virus if previously inoculated with specific immunoglobulins but not nonspecific immunoglobulins. The protective ability of IgM, whether derived from mouse or human sera, was only about 1/40 of that of IgG preparations adjusted to the same haemagglutination inhibition or neutralising titres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Thus, such prolonged viremia could result in a more pronounced infection of neuronal cells and subsequently in a more severe clinical presentation. This hypothesis is supported by previous studies of TBE patients ( 16 ) and experimentally infected laboratory animals ( 21 , 35 , 37 ), in which low concentrations of TBEV-specific antibodies and TBEV neutralizing antibodies in serum coincided with subsequent appearance of TBE and more severe disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, such prolonged viremia could result in a more pronounced infection of neuronal cells and subsequently in a more severe clinical presentation. This hypothesis is supported by previous studies of TBE patients ( 16 ) and experimentally infected laboratory animals ( 21 , 35 , 37 ), in which low concentrations of TBEV-specific antibodies and TBEV neutralizing antibodies in serum coincided with subsequent appearance of TBE and more severe disease.…”
Section: Discussionsupporting
confidence: 77%
“…However, the exact mechanism by which TBEV accesses the brain is not known ( 13 , 19 , 20 ). Furthermore, some authors reported a correlation between a low concentration of neutralizing antibodies and more severe disease, suggesting that a delayed formation of neutralizing antibodies could be associated with high viremia ( 16 , 21 ). However, no information is available on the level of viremia in patients with TBE and its effect on disease severity.…”
mentioning
confidence: 99%
“…Tick-borne encephalitis virus (TBEV), a flavivirus highly pathogenic for humans, is endemic in several European countries, Russia, and China. Transfer of monoclonal antibodies specific for TBEV E (13,25,26) or of E-specific antisera as well as of polyclonal immunoglobulin preparations with the same specificities (14,16,21) into mice resulted in protection of experimental animals from subsequent TBEV challenge, and in vivo protection by antivirion antibodies correlated with in vitro neutralization (13,25,26). In a recent study (21), we confirmed the protection of mice against a lethal intraperitoneal (i.p.)…”
supporting
confidence: 64%
“…Delayed or insufficient production of nt-ab could contribute to a more severe clinical course and higher viremia [1,5].…”
Section: Jon 1329mentioning
confidence: 99%